Aesthetic and functional management of a patient with Cornelia de Lange syndrome - Dexton Antony Johns; Dnyanesh L Bhonsale; V Y Shivashanker; Manu Johns (Wolters Kluwer Medknow Publications, 2012)
Cornelia de Lange syndrome is a syndrome of multiple congenital anomalies. The genetic and molecular bases of these lesions are not clear. It is divided into three types based on the severity of the anomaly. Dental findings revealed contracted maxilla, malaligned teeth, multiple impacted and missing teeth. This article describes the successful management of upper central incisor with lateral opening in the apical third on the mesial surface of the root along with aesthetic and functional rehabilitation.